Komposisi dan Struktur Vegetasi Riparian Strata Pohon di Kawasan Wana Wisata Curug Semirang, Ungaran, Semarang, Jawa Tengah - Pratama, Raditya; Jumari, J; Utami, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Wana Wisata Curug Semirang is a tourist area in Semarang Regency based on ecotourism. As an ecotourism area, Curug Semirang contribute as conservation area in order to protection and preservation of nature. Along with tourism development, biodiversity in Curug Semirang is increasingly threatened. The purpose of this study is to examine the composition and structure of riparian in Wana Wisata Curug Semirang Area. The method used in vegetation is a quadratic plot with a line transect. Vegetation observation was carried out at 3 stations which were divided into 15 plots covering tree strata and poles. Vegetation analysis was obtained with the value of density, dominance, frequency, and important value index. The results obtained 75 plant species covering 42 families, in the tree strata there are 16 species in 12 families, and the pole strata there are 20 species in 14 families. The highest INP of tree strata at station 1 was pine (Pinus merkusii) 180.04%, stations 2 and 3 were kemadu (Laportea sinuata) 147.53% and 102.76%, respectively. The highest IVI of the pole strata at stations 1 and 2 is coffee (Coffea arabica) 123.98% and 140.5%, and station 3 is rotan (Calamus rotang) 113%.